Breast cancer survivors and behavior: cancer care in the time of COVID-19 in Indonesia - Widyanti Soewoto (Universa Medicina, 2022)
The COVID-19 pandemic caused significant disruptions in cancer care, and preliminary research suggests that these disruptions are associated with increased levels of psychosocial distress among cancer survivors. Indonesia initially reported positive cases in early March 2020, followed by regular extensive occurrences across 34 provinces. The disease causes acute respiratory failure among people with specific comorbidities, including geriatric disorders, diabetes, cardiovascular and respiratory diseases, and cancer. Consequently, the patients’ conditions become more severe, possibly leading to a higher mortality rate. Individuals with cancer are at particularly elevated risk of a severe course of COVID-19 because they tend to be of older age and are at a greater risk for needing intensive care and for mortality. A reasonably good comprehension of the current COVID-19 outbreak, poor awareness of the primary disease and subsequent therapy program, and minimal understanding of the importance of continuing treatment during the pandemic are the probable factors causing the fear of contracting the COVID-19 virus that poses a significant threat of aggravating the existing breast cancer conditions in most patients. This anxiety shows a drastic impact in altering the behavioral patterns of survivors undergoing therapy. There is a very good understanding of how it is caused by the SARS-COV2 virus. Meanwhile, there is a severe lack of understanding of cancer and the therapeutic program. The patients are more afraid of contracting this virus than they are of their cancer. Patients prefer development of their cancer to contracting the SARS-COV2 virus. Therefore, massive education and supervision are needed for cancer patients to understand the COVID-19 pandemic and ensure that routine checks are appropriately managed.